Succession, Not Possession: Sarah’s Inheritance in Tobit - Vos, Daniel J. (The catholic biblical quarterly, 2025)
Analyses of the marriage of Tobiah and Sarah in the Book of Tobit have frequently appealed to biblical descriptions of levirate marriage to explain Tob 3:7 and 6:12, in which Tobiah is said to have the right to "inherit her." Through a closer reading of the text in light of Abraham’s complaint about the lack of an heir in Gen 15:3-4 and the Jewish Aramaic legal tradition, I argue that these verses refer to succession to Reuel’s estate through marriage to Sarah. Tobiah does not inherit Sarah, but inherits through marriage to Sarah.